Enhancing the integration of chaplains within the healthcare team A qualitative analysis of a survey study among healthcare chaplains. Issue 1 (16th February 2023) - Kruizinga, Renske; Schuhmann, Carmen; Glasner, Tina; Jacobs, Gaby
Abstract : Background: Spiritual well-being is considered an important component of health and is increasingly integrated at all levels of healthcare. Delivering good integrated spiritual care requires coordination between different colleagues in which interprofessional collaboration is crucial. However, this interprofessional collaboration is not always self-evident. What spiritual care entails, is often poorly understood by their healthcare colleagues. Developing a shared professional identity is a crucial component of the shift towards professionalisation in chaplaincy. Objectives: We aim to answer the following research question: how do healthcare chaplains in the Netherlands describe their work and their professional identity in relation to other healthcare professionals? Design and subjects: Analysis of open-ended questions of a survey among healthcare chaplains regarding professional self-understanding in the Netherlands. Results: 107 Dutch chaplains working in a healthcare setting completed the five open-ended questions in the survey. The field of healthcare chaplaincy is changing from an exclusive focus at patients, towards more activities at staff and organisational level such as educating other healthcare professionals and, being involved in ethics and policy making. Conclusions: Our research shows that the professional self-understanding of chaplains entails many leads to foster interprofessional collaboration. At the same time, there are concerns about the professional identity of the chaplain which is not always clear to every healthcare professional. Healthcare teams can benefit from an extensive integration of chaplains in the healthcare team, by including the non-patient-related activities of chaplains, such as staff training, moral deliberation and policy advice.